Efektivitas Penerapan Jobsheet pada Mata Pelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Joyo, Aldo Sastro Hamid; Elfizon, Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to analyze the effectiveness of using Jobsheets in learning the practice of Electric Motor Installation (IML) at SMK N 1 Pariaman. The results of the observation show that the implementation of the Electric Motor Installation practice has not been effective a[1]s evidenced by the lack of group discussion initiatives and students' understanding of the stages of implementing the practice is still lacking. This study uses an experimental research type with a One Group Pretest Posttest design. The subjects in the study were 32 class XI TITL students at SMK N 1 Pariaman in the 2024 academic year. Pretest and Posttest data collection used a performance assessment rubric used by teachers at SMK N 1 Pariaman. The analysis techniques used in this study are classical completeness and effect size. Based on the results of the research conducted, it can be concluded that the use of Jobsheets is very effective in class XI TITL 1 SMK N 1 Pariaman. This can be seen from the calculation of Cohen's effect size analysis showing a large category and the calculation of skill completeness indicating very effective criteria. The application of Jobsheets has a significant impact on improving student learning outcomes because it can increase students' creativity, insight and enthusiasm for learning.